Factors Affecting Women’s Motivation To Choose Entrepreneurship In East Lombok - Muh. Fahrurrozi; M. Juaini; Heru Cahyono (JMET: Journal of Management Entrepreneurship and Tourism, 2023)
This research aims to examine the effects of self-development factor (X1), family background factor (X2), and income factor (X3) partially and simultaneously on women entrepreneurship in East Lombok. Employing a descriptive quantitative, data are categorized into primary and secondary data. Population in this research is business woman in East Lombok with data sample as many as 100 people. The data were analyzed by using double linear regression t-test (partial), and f-test (simultaneous) with the regression formula MWB= 13.760 + 0,008 PD + 0,056 KLG + 0,188 PND. The result shows that the self-development variable with significant degree is as many as 0,024, significant family background as many as 0,030 and significant income as many as 0,035. Thus, it can be concluded that income affects women’s motivation of entrepreneurship in Selong District, East Lombok, since the significance value is < 0,05. The degree of F significance is 0,044 with probability 0,05, thus, it is proven that self-development variable, family background variable, and income variable affect the motivation of entrepreneurship (Y). The variable of self-development, family background, and income affect women’s motivation in entrepreneurship in Selong District as many as 56,7 %, while 58% of them are influenced by other factors beyond this research.